2020
DOI: 10.1007/s10068-020-00828-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of controlled differential sieving processing on micronutrient contents and in vivo antioxidant activities of Hibiscus sabdariffa L. calyxes powder

Abstract: Sun-dried calyxes of Hibiscus sabdariffa were finely grinded and fractionated by controlled differential sieving processing (CDSp) into four granulometric classes. The obtained powder fractions were examined for their micronutrient contents and in vivo antioxidant properties in high-fat diet induced oxidation model rats. Unsieved powder and lyophilized ethanolic extract were used for comparison. Micronutrient contents and antioxidant properties were significantly influenced (p \ 0.05) by particle sizes. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
(50 reference statements)
4
10
2
Order By: Relevance
“…The different extracts exhibited similar antiradical powers. The free radical scavenging capacity of the extracts were better than those obtained by Deli et al, (2020) [ 32 ] on H . sabdariffa fractions according to size (46.00 μg ml -1 ± 3.46 μg ml -1) for a particle size of 0–180 um.…”
Section: Resultscontrasting
confidence: 69%
“…The different extracts exhibited similar antiradical powers. The free radical scavenging capacity of the extracts were better than those obtained by Deli et al, (2020) [ 32 ] on H . sabdariffa fractions according to size (46.00 μg ml -1 ± 3.46 μg ml -1) for a particle size of 0–180 um.…”
Section: Resultscontrasting
confidence: 69%
“…The results of vitamin C content showed that small particle size fractions were more concentrated with vitamin C than large particle size fractions. These results are not similar to those found by Deli et al (2020) on the calyxes of Hibiscus sabdariffa powder fractions; they found no significant difference between the different particle size fractions. In addition, Djantou (2016) showed that, they were no significant difference (p ˂ 0.05) between mango powders of small particles size and those of large particles size.…”
Section: Vitamin Carotenoids and Saponin Contentscontrasting
confidence: 99%
“…Our study showed that the ethanolic extract has shown high vitamin C content compared to all CDSp powder fractions of D. mespilifomis fruits. These results are similar to those found by Deli et al (2020) on the CDSp powder fractions and ethanolic extract of the calyxes of H. sabdariffa. The abundance of vitamins C in the fractions of < 50 µm may be explained by the fact that the finest particles would be individualized during grinding and would pass preferentially to the smaller particle size during sieving.…”
Section: Vitamin Carotenoids and Saponin Contentssupporting
confidence: 91%
See 1 more Smart Citation
“…Using this technique, many authors demonstrated that powder fractionation resulted in concentrating polyphenols in finer particle size [20] [21] [22]. Otherwise, our previous study reported that finer fractions (<180 µm and 180 -212 µm) of Dichrostachys glomerata, Adansonia digitata, Boscia senegalensis and Hibiscus sabdariffa concentrated more polyphenols, micronu-trients and antioxidant activities as ethanolic extract [23] [24] [25]. However, there is no study on the effect of powder fractionation on the EO phytochemicals in relation to their antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%